2022
DOI: 10.3389/fnut.2022.914079
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides ameliorate high-fat diet-induced non-alcoholic steatohepatitis via farnesoid X receptor activation

Abstract: BackgroundGypenosides (Gyps), the major botanical component of Gynostemma pentaphyllum, was found to up-regulate the farnesoid X receptor (FXR) in a mouse model of non-alcoholic steatohepatitis (NASH). However, the exact role of FXR and underlying mechanisms in Gyps-mediated effects on NASH remain to be elucidated.PurposeThis study investigated whether Gyps attenuates NASH through directly activating FXR in high-fat diet (HFD)-induced NASH, and delineated the molecular pathways involved.Study designA mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These components possess potential applications in medicine and food due to their diverse pharmacological activities including anti-inflammatory, antioxidation, antifibrosis, antiobesity, hepatoprotective, and lipid-lowering effects [ 27 29 ]. Notably, G. pentaphyllum and gypenosides have shown promise in alleviating hepatic steatosis, mitochondrial impairment, and inflammatory response, ultimately improving liver dysfunction, particularly in cases of fatty liver [ 28 , 40 ]. Furthermore, cinnamon has demonstrated therapeutic benefits by reducing hyperlipidemia, liver enzymes, insulin resistance, and hepatic steatosis in both NAFLD patients and animal models [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These components possess potential applications in medicine and food due to their diverse pharmacological activities including anti-inflammatory, antioxidation, antifibrosis, antiobesity, hepatoprotective, and lipid-lowering effects [ 27 29 ]. Notably, G. pentaphyllum and gypenosides have shown promise in alleviating hepatic steatosis, mitochondrial impairment, and inflammatory response, ultimately improving liver dysfunction, particularly in cases of fatty liver [ 28 , 40 ]. Furthermore, cinnamon has demonstrated therapeutic benefits by reducing hyperlipidemia, liver enzymes, insulin resistance, and hepatic steatosis in both NAFLD patients and animal models [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…AST and ALT are widely distributed in various tissues, especially in the liver. Increased AST levels can be used as an indicator of mitochondrial damage, while high ALT levels suggest membrane damage ( 29 ). When the liver function or structure is damaged, these transaminases are released from the liver increasing their serum levels.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 It has also been prescribed as traditional Chinese medicine to treat various diseases, such as non-alcoholic steatohepatitis (NASH) and diabetes. 6 Previous phytochemical investigations showed that the dammarane triterpenoid saponins, sterols and flavonoids were the major chemical constituents in G. pentaphyllum . 7 , 8 To date, more than 180 dammarane triterpenoid saponins were reported from G. pentaphyllum with various bioactivities including antioxidant, antidiabetic, anti-inflammatory, hepatoprotective and antitumor effects.…”
Section: Introductionmentioning
confidence: 99%